2017
DOI: 10.1038/modpathol.2017.32
|View full text |Cite
|
Sign up to set email alerts
|

Genomic profiling of breast secretory carcinomas reveals distinct genetics from other breast cancers and similarity to mammary analog secretory carcinomas

Abstract: Secretory carcinomas of the breast are rare tumors with distinct histologic features, recurrent t(12;15)(p13;q25) translocation resulting in ETV6-NTRK3 gene fusion and indolent clinical behavior. Mammary analog secretory carcinomas arising in other sites are histopathologically similar to the breast tumors and also harbor ETV6-NTRK3 fusions. Breast secretory carcinomas are often triple (estrogen and progesterone receptor, HER2) negative with a basal-like immunophenotype. However, genomic studies are lacking, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 86 publications
2
65
1
3
Order By: Relevance
“…In their immunohistochemical and genomic review of secretory carcinoma of the breast and mammary analogue secretory carcinoma, Krings et al reported 44% of their SCB cases (four of nine tumours) demonstrated weak to moderate ER expression. 25 Within our study cohort, seven patients (50%) were found to have tumours with ER expression. These patients tended to be older, and five of the seven patients received hormonal therapy (Table 1).…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…In their immunohistochemical and genomic review of secretory carcinoma of the breast and mammary analogue secretory carcinoma, Krings et al reported 44% of their SCB cases (four of nine tumours) demonstrated weak to moderate ER expression. 25 Within our study cohort, seven patients (50%) were found to have tumours with ER expression. These patients tended to be older, and five of the seven patients received hormonal therapy (Table 1).…”
Section: Discussionmentioning
confidence: 81%
“…[51][52][53][54] Krings et al reported massively parallel sequencing analysis of nine secretory breast carcinomas and demonstrated very low mutation burdens and very few copy number alterations in these tumours. 25 In all cases of SCB with distant metastases in the literature, no additional molecular alterations were reported.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, these studies have generally not included triple‐negative salivary gland‐like tumours that can arise in the breast, including secretory carcinomas, acinic cell carcinomas and adenoid cystic carcinomas, as well as MEC and even more rare types . Recent studies suggest that secretory carcinomas and adenoid cystic carcinomas of the breast are genetically more similar to their respective salivary gland counterparts than they are to other triple‐negative carcinomas . In contrast, acinic cell carcinomas arising in the breast harbour frequent TP53 mutations and complex patterns of copy number alterations which are not present in salivary gland acinic cell carcinomas, suggesting that these two tumours are not related despite their histological similarity .…”
Section: Discussionmentioning
confidence: 99%